The Effect of Leadership, Apparatus Professionality, and Work Facilities on the Quality of Ship Services and Goods in the Main Port Authority Office of Tanjung Priok - Hermanta, Hermanta; Adiwisastra, Josy; Hubeis, Musa; Sulistyani, Dewi (International Journal Papier Public Review, 2020)
This study aims to determine the effect of leadership, the professionalism of the apparatus and work facilities on the quality of service both partially and collectively. The sampling technique in this study was proportionate stratified random sampling with a sample of 313 respondents. This research method is a quantitative method with regression analysis. Data collection techniques using documentation techniques, literature study, questionnaires, and observations. The research data collection tool was a questionnaire based on a Likert scale. The data analysis techniques in this study were validity test, reliability test, normality test, linearity test, multicollinearity test, heteroscedasticity test, F test and t-test, simple and multiple linear regression. The results of the study prove that there is a positive influence of leadership on service quality by 82%. Second, there is a positive influence on the professionalism of the officers on the quality of service by 79.3%. Third, there is a positive effect of work facilities on service quality by 80.2%. Fourth, there is a positive influence of leadership, apparatus professionality, and work facilities together on service quality of 83.9%. The quality of ship and goods services at the Tanjung Priok Main Port Authority Office can be achieved through effective leadership, a high level of professionalism of the officials, and adequate work facilities. These three variables must be considered so that the quality of ship and goods services can satisfy service users.